TRADISI MANDI SAFAR DESA SUNGAI BULUH KECAMATAN SINGKEP BARAT KABUPATEN LINGGA PROVINSI KEPULAUAN RIAU - Restu Aditiya; Swis Tantoro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study titled tradition take a bath Safar of countryside Sungai Buluh, subdistrict West Singkep, Lingga Regency, Riau Islands Province Based on the historical tradition in the countryside of Sungai Buluh Safar Bath has been done during the Lingga Sultanate, Sultan Abdurrahman Muadzam Syah II (1885-1911). Safar bath made Sungai Buluh rural communities is to maintain the countryside of disasters and to expel the plague to society.This study aims to describe the process of implementation of Tradition Take a Bath Safar, to analyze the meaning and symbols contained in the implementation of Tradition Take a Bath Safar. This research was conducted by using a snowball sampling approach (observation and in-depth interviews to collect data) that includes the head of the village and devices, religious leaders, community leaders.To analyze the data descriptive qualitative research conducted on data collected later in the mentioned descriptively that describe or narrate the results with a description of logical sentences to be understandable and easy to understand.This research was conducted in the countryside of Sungai Buluh, Subdistrict West Singkep, Lingga Regency, Riau Islands Province. The results show the meaning research Tradition Take a Bath Safar conducted to resident teach religion through culture that can be seen from the writing wafaq taken from some fragments of verses the al-Quran. Meaning Safar bath can provide a sense of security, as well as treatment.Keywords: Process,Safar Bath, Tradition